Modern problems and prospects of complex physical, mathematical and numerical modelling of hydro- and gas dynamics, conjugated heat- and mass transfer at inert and chemical reacting mixes flow in internal systems; Проблемы геологии и освоения недр; Т. 2 - Kharlamov (Harlamov) S. N. Sergey Nikolaevich (Моделирование процессов при транспортировке нефти и газа, 2012)
Заглавие с титульного листа